Sistem Kontrol Keamanan Door-Lock Selenoid Berbasis Arduino - Zuriati, Zuriati; Irfan, Abdurrahman; Pratama, I Gede Wahyu; Azim, Rosi Dina Fauzan (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2023)
Storage lockers make a lot of sense to people nowadays, whether in the center of the world, sports facilities like basketball courts, gyms, swimming pools, Schools, workplaces and many more places where there is a great need for them. Usually lockers only use cards or keys which can be easily dismantled by criminals. Therefore, the Arduino-Based DOOR LOCK Security Control System on Lockers is very much needed in the current era. Because there are so many crimes that are rampant, especially in storage areas or lockers The increasing demand for technology with little human intervention has made the pace of development of automatic control science very rapid. With the